2011
DOI: 10.1093/hmg/ddr545
|View full text |Cite
|
Sign up to set email alerts
|

BLM helicase facilitates RNA polymerase I-mediated ribosomal RNA transcription

Abstract: Bloom's syndrome (BS) is an autosomal recessive disorder that is invariably characterized by severe growth retardation and cancer predisposition. The Bloom's syndrome helicase (BLM), mutations of which lead to BS, localizes to promyelocytic leukemia protein bodies and to the nucleolus of the cell, the site of RNA polymerase I-mediated ribosomal RNA (rRNA) transcription. rRNA transcription is fundamental for ribosome biogenesis and therefore protein synthesis, cellular growth and proliferation; its inhibition l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 53 publications
3
74
0
Order By: Relevance
“…A reduction in RNAPII transcription in permeabilized WS cells has also been reported [145]. In addition to CS, Bloom’s and Werner’s, growth defects are also observed in patients with other “ribosomopathies” as well, further supporting a link between abnormal RNAPI transcription and growth deficiency [144]. …”
Section: An Expanded Version Of the Transcription Syndrome Hypothementioning
confidence: 74%
See 1 more Smart Citation
“…A reduction in RNAPII transcription in permeabilized WS cells has also been reported [145]. In addition to CS, Bloom’s and Werner’s, growth defects are also observed in patients with other “ribosomopathies” as well, further supporting a link between abnormal RNAPI transcription and growth deficiency [144]. …”
Section: An Expanded Version Of the Transcription Syndrome Hypothementioning
confidence: 74%
“…Thus a defect in transcription of rRNA genes provides a simple explanation for growth defects observed in CS patients, one of the canonical features of the disease. Interestingly, patients with Werner’s syndrome and Bloom’s syndrome have growth defects, and reduced nucleolar transcription has been described in cells from both diseases [143, 144]. A reduction in RNAPII transcription in permeabilized WS cells has also been reported [145].…”
Section: An Expanded Version Of the Transcription Syndrome Hypothementioning
confidence: 99%
“…BLM, however, has been localized to the nucleolus by immunofluorescence 70, 71 , and co-immunoprecipitates the RNAPI subunit, RPA194 71 . Functionally, it has been shown that BLM facilitates the transcription of the pre-rRNA though its helicase activity on the rDNA 71 . Pulse-chase analysis for instance in BLM-deficient cells reveals a decrease in the production of the 45S pre-rRNA primary transcript 71 .…”
Section: Functional Roles For Dna Repair Proteins In the Nucleolusmentioning
confidence: 99%
“…Functionally, it has been shown that BLM facilitates the transcription of the pre-rRNA though its helicase activity on the rDNA 71 . Pulse-chase analysis for instance in BLM-deficient cells reveals a decrease in the production of the 45S pre-rRNA primary transcript 71 . Defects in pre-rRNA transcription can lead to decreases in mature 18S and 28S rRNA species, and/or the triggering of the cell stress response and apoptosis 72 .…”
Section: Functional Roles For Dna Repair Proteins In the Nucleolusmentioning
confidence: 99%
“…In about one-third of cells, BLM localizes to the nucleolus, arranged in a large number of irregularly shaped, closely associated blobs. BLM function in the nucleolus is important for rDNA transcription [Grierson et al, 2012] and interaction between BLM, and topoisomerase I is critical to this function [Grierson et al, 2013]. In cells treated with agents that damage DNA, particularly agents that affect the progression of replication forks, BLM concentrates focally to stalled or damaged replication forks.…”
Section: Regulation Of the Subnuclear Localization Of The Blm Proteinmentioning
confidence: 99%